The use of the rock mass variability index in material property selection for pit slope stability modelling - Narendranathan, Sanjive (Curtin University, 2010)
The primary aim of this research is to put forward a new process which would enhance the methodology which rock mechanics practitioners apply to formulate material parameters for the purpose of slope stability modelling. Often a great deal of emphasis is placed on the actual modelling process itself i.e. the type of software number of nodes etc but very little consideration is given to what is actually being fed into these software packages.The Rock Mass Variability Index is a method being introduced by the author to aid practitioners in the process of calculating material properties for the purposes of stability modelling based on assessing and quantifying their statistical variability. To date though, there have been many different variations of probabilistic slope design approaches put forward by others; there is not one unified system to assess material strength variability. This is left to the discretion of the particular practitioner.